Obtencion de proteinas de salvado de arroz. II. Parte: Precipitacion - Ledesma, L.=700 1 Fuertes, S.; Placencia, V.; Zumbado, H.
(Es, En)
Ilus., 16 ref.
Keywords: ORYZA SATIVA; SALVADO; TECNICAS DE LABORATORIO; PRECIPITACION QUIMICA; PROTEINAS; PH; TEMPERATURA; DURACION; CUBA; CIENCIA Y TECNICA EN LA AGRICULTURA: ARROZ